Providing the right medication monitoring. Issue 8 (August 2013) - Avery, Tony; Gookey, Gill; Spencer, Rachel; Knox, Richard; Marsden, Kate; Salema, Ndeshi
In order for medication to be prescribed effectively and safely, many medications require monitoring. Medication monitoring may involve blood tests but can also include other monitoring such as blood pressure, weight or electrocardiograms. Monitoring can be required before initiating medication, soon after starting, or regularly over the course of treatment. Ensuring that this monitoring has been undertaken is an important part of medication review involving repeat prescribing. The General Medical Council-funded PRACtICe study looked at prescribing and monitoring errors in primary care. Out of the 302 errors identified, 55 (18%) were monitoring errors. Of those drugs that required blood test monitoring, 7% of prescriptions contained a monitoring error. This article gives the reader opportunities to reflect upon different scenarios that involve medication that requires monitoring decisions and how monitoring could be managed in primary care. There are also suggestions for additional continuing professional development activities.